Characterization of Oil Extracted from Red Pitaya (Hylocereus polyrhizus) Seeds using Supercritical Fluid Extraction - Abdullah, Asiah; Salwa Abd Gani, Siti; Fadzillah Mohd Mokhtar, Nor; Yap Yun Hin1, Taufiq; Abdul Haiyee, Zaibunnisa (International Journal of Engineering and Technology, 2018)
Hylocereus polyrhizus or red pitaya is one of the commercially planted crops in southeast Asia for fruit. The seeds are disposed as a by-product in pitaya juice manufacturing. In this study, supercritical fluid extraction (SFE) was performed to obtain oil from red pitaya seeds. The chemical composition of extracted oil was identified by gas chromatography-mass spectrometry (GC-MS) analysis. The analysis revealed that the extracted oil consist mainly of polyunsaturated fatty acid (PUFA) with linoleic acid as its main constituents. The extracted oil was further analyzed by Fourier-transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and tested for its antimicrobial activity to characterize the oil quality. In general, DSC and TGA analysis showed high thermal stability profile of red pitaya seed oil and antimicrobial activity test showed that the extracted oil exhibited slightly inhibitory effect against gram-positive bacteria named Staphylococcus aureus.Â Â